2019
DOI: 10.1002/apj.2352
|View full text |Cite
|
Sign up to set email alerts
|

Impact of shale on properties and oil recovery potential of sandstone formation for low‐salinity waterflooding applications

Abstract: Porous and permeable formation, namely, sandstone, may also contain water-reactive clays that swell in the presence of water and cause damage to formation by reducing its permeability. The inclusion of salts in injected water (called low-salinity water) is considered successful to inhibit shale swelling. Therefore, this study reports the impact of shale content (0-25%) on porous and permeable sand-packs in the presence of fresh water and salt solutions (KCl/CaCl2, 0-4 wt%). The properties of sand-packs were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Increasing amounts of oily wastewaters are produced all over the world by several industrial activities (such as oil refining and metal and food industries 1,2 ) and also during the continuous cleaning of the increasing amount of registered vehicles—it is estimated to be 2 billion until 2035 3,4 . These wastewaters contain several contaminations that has been proven to pose serious risks to both the natural environment and human health 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing amounts of oily wastewaters are produced all over the world by several industrial activities (such as oil refining and metal and food industries 1,2 ) and also during the continuous cleaning of the increasing amount of registered vehicles—it is estimated to be 2 billion until 2035 3,4 . These wastewaters contain several contaminations that has been proven to pose serious risks to both the natural environment and human health 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“…To characterize the sand particles, scanning electron microscopy (SEM) and XRD (X-ray diffraction) analysis were performed. The results of SEM and XRD analysis are provided in our previous studies (Chaturvedi et al, 2019b;Goswami et al, 2018). From the obtained micrographs of SEM, it was established that the sand particles used were of the size 200-380 mm.…”
Section: Sand-pack Preparation and Flooding Experimentsmentioning
confidence: 96%
“…Literature studies on LSW have shown an increase in oil recovery by 8-20% over conventional water flooding. In addition, water-induced swelling of shale particles can be reduced by tuning the concentration of salt ions, which will make shaly-sandstone (an unconventional rock) more productive through the improvement in its petro-physical properties (Chaturvedi et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The sand used in this study had a uniform size which ranged from 200-380 µm. These fabricated sand packs closely resemble the oil reservoirs of sandstone origin and are hence most apt for this study [6,31]. The sand used in this study was characterized using an XRD machine (X-Ray Diffractometer D8 Advance, Bruker, India) and the mineral composition of the sand was defined as quartz (88 wt%), kaolinite (6 wt%), feldspar (2 wt%) and chlorite (1 wt%) [32].…”
Section: Nanoparticle Retention Experimentsmentioning
confidence: 99%